Effects of tropical weeds on yield in white yam (Dioscorea rotundata Poir) - Unamma, R.P.; Akobundu, I. (Wiley, 1989)
The effects of tropical weeds on the yield of while yam were studied outdoors in wooden boxes. When the foliage and roots of weeds were in physical contact with the crop until harvest (full interference), tuber yield of yam was reduced by 76–79% of that obtained under weed‐free conditions over 3 years of study. When there was no physical contact between roots of crop and weeds, the leachate from the weed zone caused tuber yield reductions of 42, 40 and 38% in 1978, 1979 and 1980, respectively, when it was applied to the yam zone. This leachate also reduced leaf area index (LAI) in the yam crop but the adverse effects on yam root and shoot biomass were less pronounced. This technique made it possible to separate competitive interference from allelopathic interference of tropical weeds with the yam crop.